2005
DOI: 10.1159/000086200
|View full text |Cite
|
Sign up to set email alerts
|

Why Look in the Brain for Answers to Temporomandibular Disorder Pain?

Abstract: Temporomandibular disorder (TMD) patients often exhibit widespread clinical pain, as well as greater sensitivity to experimental pain than pain-free controls, suggesting a role of central pathophysiologic mechanisms in TMD. Moreover, TMD is more prevalent among women, which may be related to the higher sensitivity of women to experimental pain. Women also exhibit greater temporal summation of heat pain compared to men. Temporal summation, the increase in pain intensity upon repetitive noxious stimulation of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
14

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 92 publications
2
83
0
14
Order By: Relevance
“…Nociceptive impulses from the head and neck muscles can produce a continuous afferent bombardment for the caudal trigeminal nucleus (20) and generate pain in the orofacial region (21) . The nociceptive input can be adjusted to a condition of pathological hyperexcitability and contribute to the development or maintenance of chronic pain, but also increase the likelihood of other pain disorders (22) . The results of this study showed that individuals with TMD showed greater asymmetry in the activation of the AT muscle during mastication's AP .…”
Section: Discussionmentioning
confidence: 99%
“…Nociceptive impulses from the head and neck muscles can produce a continuous afferent bombardment for the caudal trigeminal nucleus (20) and generate pain in the orofacial region (21) . The nociceptive input can be adjusted to a condition of pathological hyperexcitability and contribute to the development or maintenance of chronic pain, but also increase the likelihood of other pain disorders (22) . The results of this study showed that individuals with TMD showed greater asymmetry in the activation of the AT muscle during mastication's AP .…”
Section: Discussionmentioning
confidence: 99%
“…TMD are characterized by throbbing, tender, continuous pain and result from or are initiated by activation of nociceptors in the temporomandibular joint and/or muscles of mastication (Sarlani and Greenspan, 2005;Ro, 2008;Sessle et al, 2008;Manfredini and Nardini, 2010). In contrast, trigeminal neuralgia is characterized by intermittent periods of sharp, electricity-like, shooting pain that results primarily from compression of the trigeminal root entry zone by an arterial vessel (Meaney et al, 1995;Hamlyn, 1997).…”
Section: Neuropathic Pain and The Thalamusmentioning
confidence: 99%
“…Furthermore, VP thalamic stimulation can produce pain (Lenz et al, 1993;Davis et al, 1996) and increased thalamic bursting activity and biochemical changes indicative of neuronal loss occur in patients with pain after spinal cord injury (Lenz et al, 1989;Pattany et al, 2002). In direct contrast to neuropathic pain conditions, pain associated with temporomandibular disorders (TMD) results primarily from the activation of peripheral nociceptors (Sarlani and Greenspan, 2005;Ro, 2008;Sessle et al, 2008;Manfredini and Nardini, 2010) and, furthermore, is associated with thalamic gray matter volume increases (Younger et al, 2010). Given this, it is possible that the thalamus plays differential roles in the maintenance and/or generation of different forms of chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…All TMD patients were examined and diagnosed using the Research Diagnostic Criteria for TMD (Dworkin and LeResche, 1992) and all PTN patients were diagnosed using the Liverpool Criteria (Nurmikko and Eldridge, 2001). TMD is thought to result primarily from the activation of peripheral nociceptors (Sarlani and Greenspan, 2005;Ro, 2008;Manfredini and Nardini, 2010), although it may also contain a small neuropathic component. In contrast, PTN is commonly associated with a structural lesion or systematic disease and may result from direct trauma to the nerve.…”
Section: Subjectsmentioning
confidence: 99%